The Development of DC-DC Buck Converter with Practical Design Methods - Cebeci, Emre; Yasa, Yusuf (IEEE, 2016)
In this paper, DC-DC buck converter is designed and analyzed which have 100V/50A output values. The general ideas about operating the buck converter operation is mentioned then design steps are given, respectively. All active and passive elements values of the buck converter circuit are determined and the controller design is done using MatlabSISO tool. Finally, the simulation is executed on MatlabSimulink software and the related result are provided and compared with the theoretical results.
Keywords: Engineering